Survival of Respiratory Failure within the First 72 Hours in Preterm Infants with Respiratory Distress Based on the Downes Score Assessment - Wedi Iskandar; Hana Sofia Rachman; Vidi Permata Galih; Forestiera Indikurnia; Muhammad Hafizh (Mashhad University of Medical Sciences, 2022)
Background: Respiratory distress in neonates is the most common condition of preterm infants receiving treatment in the neonatal intensive care unit. As a clinical assessment of respiratory distress, the Downes score can predict the risk of respiratory failure. The present study aimed to determine the survival of respiratory failure in the first 72 h in preterm infants with respiratory distress based on the Downes score assessment.Methods: A prospective cohort survival analysis was performed at three hospitals in Indonesia (Al-Islam Hospital, Bandung, Al-Ihsan Hospital, Bandung, and Cibabat Hospital, Cimahi) from April to July 2021. Subjects were infants aged 28-36 weeks, with respiratory distress based on the Downes score within the first 2, 6, 12, 24, 48, and 72 h after delivery. The analyzed variables included birth weight ([BW], <1500 vs. 1500-2500 g), gestational age ([GA], 28-32 vs. 32-37 weeks), and 5-min APGAR score (<7 vs. >7). Bivariate and multivariate analyses were conducted with Cox regression proportional hazard and the Kaplan-Meier estimate of survival rate was also performed. In addition, the adjusted hazard ratio (aHR) was calculated, and a P-value of less than 0.05 was considered statistically significant.Results: Of the 89 subjects who met the criteria, 20 (22.47%) experienced respiratory failure. The multivariate analysis including BW (aHR: 1.846, 95%CI: 0.570-5.979, P> 0.05), GA (aHR: 2.273, 95 %CI: 0.697-7.416, P>0.05), and the 5-min APGAR score (aHR: 2.049, 95%CI: 0.811-5.179, P>0.05) estimated the survival rate for respiratory failure at the age of 72 h at 74.7% (standard error: 0.05%).Conclusion: A GA of <32 weeks, a BW of <1500 g, and the condition of asphyxia simultaneously increased the aHR of respiratory failure, with an estimated survival rate of 74.7%.